KEPUASAN IBU HAMIL TERHADAP PELAYANAN ANC PADA MASA PANDEMI COVID-19 - Rohani; Veradilla; Indri Kusyani (LPPM STIKes Mitra Adiguna, 2022)
The maternal mortality rate in Southeast Asian countries is Indonesia 214 per 100,000 live births, Philippines 170 per 100,000 live births, Thailand 44 per 100,000 live births, Brunei 60 per 100,000 live births, and Malaysia 39 per 100,000 live births. In providing services, midwives or officers must create good relationships with patients and their families. The purpose of this study was to describe the satisfaction of pregnant women with ANC services during the covid-19 pandemic at the Citra Clinic. This research method is analytic with a quantitative approach. This research uses a descriptive method. The descriptive method is to explain the description of pregnant women's satisfaction with antenatal care during the covid-19 pandemic. The results of this study obtained a distribution of the frequency of registration services for 8 respondents (26.7%) who were satisfied with the registration service. Distribution of the frequency of midwife services 8 respondents (26.7%) were satisfied with the services of midwives. The frequency distribution of attitudes of 29 respondents (96.7%) were satisfied with the attitude of the midwife. Distribution of the frequency of completeness of facilities and infrastructure 26 respondents (86.7%) were satisfied with the completeness of facilities and infrastructure. This suggestion can be used as input for health workers, especially those at the Citra Clinic to find out a description of the satisfaction of pregnant women with ANC services. Keywords: ANC Service Satisfaction, Pregnant Women, Coronavirus Disease Reference : (2016-2021)